Combined influence of steel fibers and microsilica on the mechanical performance of concrete for rigid pavements (Gaceta Técnica, 2026)
The objective of the research was to analyze the mechanical behavior of concrete containing microsilica and steel fibers, particularly for use in rigid pavements. With this purpose, 108 specimens—including beams and test cylinders—were produced and subjected to stresses typical of pavement slabs: tension, flexure, and compression. Four combinations were developed: a standard concrete mix and three modified mixes containing steel fibers (1%, 2%, and 3%) and microsilica (5%, 7,5%, and 10%). Satisfactory results were obtained at 28 days, with mix M2 (2% steel fiber + 7.5% microsilica) demonstrating the best performance, achieving a compressive strength of 24,58 MPa, a flexural strength of 4,18 MPa, and a tensile strength of 2,60 MPa. The combination of these two additives yielded the best structural performance, highlighting their potential to enhance pavement durability and mitigate early-stage failures in rigid concrete structures
Keywords: fiber-reinforced concrete; microsilica; rigid pavements; mechanical strength of concrete; concrete durability